单向离合器对皮带传动系统振动特性影响研究 - 曹登峰 (Jixie chuandong)
The vibration models of a automobile belt drive system contains of two pulley,the belt and one-way clutch are established,by using numerical analysis method,the vibration characteristic of the belt drive system and the effect of one-way clutch on the belt drive system vibration characteristics are studied.The analysis results show that the input shaft and the pulley angular displacement,displacement and the clutch torque show cyclical changes,the one-way clutch can reduce the vibration of the input shaft,pulley and the clutch torque of transmission system,and change its motion form,the pulley and the input shaft and belt span resonance region are basically identical,but the pulley and the input shaft resonance region than the belt resonance region wide.